Genotypic and mechanistic characterization of subtype-specific hiv adaptation to host cellular immunity - Kinloch, Natalie N; Lee, Guinevere Q; Carlson, Jonathan M.; Jin, Steven W; Brumme, Chanson J; Byakwaga, Helen; Muzoora, Conrad; Bwana, Mwebesa B; Cobarrubias, Kyle D; Hunt, Peter W; Martin, Jeff N; Carrington, Mary; et al. (Journal of Virology, 2019)
ABSTRACT The extent to which viral genetic context influences HIV adaptation to human leukocyte antigen (HLA) class I-restricted immune pressures remains incompletely understood. The Ugandan HIV epidemic, where major pandemic group M subtypes A1 and D cocirculate in a single host population, provides an opportunity to investigate this question. We characterized plasma HIV RNA gag, pol, and nef sequences, along with host HLA genotypes, in 464 antiretroviral-naive individuals chronically infected with HIV subtype A1 or D. Using phylogenetically informed statistical approaches, we identified HLA-associated polymorphisms and formally compared their strengths of selection between viral subtypes. A substantial number (32%) of HLA-associated polymorphisms identified in subtype A1 and/or D had previously been reported in subtype B, C, and/or circulating recombinant form 01_AE (CRF01_AE), confirming the shared nature of many HLA-driven escape pathways regardless of viral genetic context. Nevertheless, 34% of the identified HLA-associated polymorphisms were significantly differentially selected between subtypes A1 and D. Experimental investigation of select examples of subtype-specific escape revealed distinct underlying mechanisms with important implications for vaccine design: whereas some were attributable to subtype-specific sequence variation that influenced epitope-HLA binding, others were attributable to differential mutational barriers to immune escape. Overall, our results confirm that HIV genetic context is a key modulator of viral adaptation to host cellular immunity and highlight the power of combined bioinformatic and mechanistic studies, paired with knowledge of epitope immunogenicity, to identify appropriate viral regions for inclusion in subtype-specific and universal HIV vaccine strategies. IMPORTANCE The identification of HIV polymorphisms reproducibly selected under pressure by specific HLA alleles and the elucidation of their impact on viral function can help identify immunogenic viral regions where immune escape incurs a fitness cost. However, our knowledge of HLA-driven escape pathways and their functional costs is largely limited to HIV subtype B and, to a lesser extent, subtype C. Our study represents the first characterization of HLA-driven adaptation pathways in HIV subtypes A1 and D, which dominate in East Africa, and the first statistically rigorous characterization of differential HLA-driven escape across viral subtypes. The results support a considerable impact of viral genetic context on HIV adaptation to host HLA, where HIV subtype-specific sequence variation influences both epitope-HLA binding and the fitness costs of escape. Integrated bioinformatic and mechanistic characterization of these and other instances of differential escape could aid rational cytotoxic T-lymphocyte-based vaccine immunogen selection for both subtype-specific and universal HIV vaccines.